2013
DOI: 10.1007/s00424-013-1407-9
|View full text |Cite
|
Sign up to set email alerts
|

The sodium chloride cotransporter SLC12A3: new roles in sodium, potassium, and blood pressure regulation

Abstract: SLC12A3 encodes the thiazide-sensitive sodium chloride cotransporter (NCC), which is primarily expressed in the kidney, but also in intestine and bone. In the kidney, NCC is located in the apical plasma membrane of epithelial cells in the distal convoluted tubule. Although NCC reabsorbs only 5 to 10 % of filtered sodium, it is important for the fine-tuning of renal sodium excretion in response to various hormonal and non-hormonal stimuli. Several new roles for NCC in the regulation of sodium, potassium, and bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
47
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 144 publications
1
47
0
Order By: Relevance
“…In animals, it has been reported that a cation-chloride cotransporter (CCC) family (also called SLC12) is involved in transport of K + , Na + , and Cl 2 (Russell, 2000;Hebert et al, 2004;Gamba, 2005 (Hoffmann et al, 2009;Lindinger et al, 2011;Moes et al, 2014). CCC family genes were also found in the plant genome, but only a few of them have been functionally characterized.…”
mentioning
confidence: 99%
“…In animals, it has been reported that a cation-chloride cotransporter (CCC) family (also called SLC12) is involved in transport of K + , Na + , and Cl 2 (Russell, 2000;Hebert et al, 2004;Gamba, 2005 (Hoffmann et al, 2009;Lindinger et al, 2011;Moes et al, 2014). CCC family genes were also found in the plant genome, but only a few of them have been functionally characterized.…”
mentioning
confidence: 99%
“…5,6 Although the canonical action of aldosterone is to increase epithelial Na + channel (ENaC) activity, it is accepted that aldosterone also stimulates the thiazide-sensitive Na + -Cl 2 cotransporter (NCC). 7,8 Aldosterone infusion increases NCC activity 9 and NCC abundance. 10 Dietary salt restriction increases the abundance of phosphorylated (activated) Na + -Cl 2 cotransporter (pNCC).…”
mentioning
confidence: 99%
“…Several members of the electroneutral cotransporter gene family are potentially implicated in hypertension, such as NKCC2 [83], KCC3 [84], TSC [85], epithelial sodium channel [86], and renal epithelial chloride channel [87]. Besides that TSC is the target of thiazide diuretics that are used in treatment of hypertension [9], it was reported that null mutant (TSC −/− ) mice carried a lower blood pressure than wild-type mice during Na + restriction in animal models [88].…”
Section: Association Between Tsc Mutants and Hypertensionmentioning
confidence: 99%
“…Nedd4-2 is a ubiquitinase which induces ubiquitylation of TSC and decreases its activity and surface expression in vitro and in vivo, while SGK1 could prevent these effects [118]. In addition, Cullin-3 and Kelch-like 3, two ubiquitinases, were also found to regulate TSC via ubiquitinating WNK4 [85]. Protein kinase network regulates TSC activity via phosphorylation and ubiquitylation, and we expect that this complex network system may help to identify patients with hypertension and can be the choice of antihypertensive medication in the future.…”
mentioning
confidence: 99%
See 1 more Smart Citation